Socio‐economic, behavioural, (neuro)psychological and clinical determinants of HRQoL in people living with HIV in Belgium: a pilot study. Issue 1 (12th December 2013) - Degroote, Sophie; Vogelaers, Dirk P.; Vermeir, Peter; Mariman, An; De Rick, Ann; Van Der Gucht, Bea; Pelgrom, Jolanda; Van Wanzeele, Filip; Verhofstede, Chris; Vandijck, Dominique M.
Abstract : Introduction: Due to highly active antiretroviral therapy (HAART), HIV‐1 infection has evolved from a lethal to a chronic disease. As such, health‐related quality of life (HRQoL) has become an important outcome variable. The purpose of this study was to identify socio‐economic, behavioural, (neuro)psychological and clinical determinants of HRQoL among people living with HIV (PLHIV). Methods: This study was conducted between 1 January and 31 December 2012 at the AIDS Reference Centre of Ghent University Hospital, a tertiary care referral centre in Belgium. Validated self‐report questionnaires were administered to collect socio‐demographic data, to assess HRQoL (Medical Outcomes Study‐HIV), depressive symptoms (Beck Depression Inventory‐II) and adherence to HAART (Short Medication Adherence Questionnaire) and to screen for neurocognitive dysfunction. Results: A total of 237 people participated, among whom 187 (78.9%) were male. Mean age was 45.8±10.7 years and 144 (63.7%, 144/226) participants were homosexual. Median physical and mental health score (PHS, MHS) were 55.6 (IQR 48.2–60.6) and 52.0 (IQR 44.2–57.9), respectively. Multivariable regression analysis revealed that incapacity to work, depressive symptoms, neurocognitive complaints (NCCs), dissatisfaction with the patient–physician relationship and non‐adherence were all negatively associated with HRQoL. Conclusions: Socio‐economic (work status), behavioural (adherence) and (neuro)psychological (depressive symptoms, NCCs) determinants independently impact HRQoL among this cohort of PLHIV. Clinical parameters (viral load, CD4 cell count) were not independently associated with HRQoL.